2010
DOI: 10.1002/cncr.25544
|View full text |Cite
|
Sign up to set email alerts
|

The effects of body mass index on complications and survival outcomes in patients with cervical carcinoma undergoing curative chemoradiation therapy

Abstract: Background The effect of body mass index (BMI) on treatment outcomes for patients with locally advanced cervical carcinoma undergoing definitive chemoradiation is unclear. Methods This study cohort included all cervical carcinoma patients (n = 404) with stage IB1 and positive lymph nodes or stage ≥ IB2 treated at our facility from January 1998 to January 2008. Mean follow-up time was 47.2 months. BMI was calculated using the National Institute of Health online calculator. BMI categories were created accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 26 publications
3
55
1
Order By: Relevance
“…These studies focused primarily on the prognostic value of being overweight or obese. On the other hand, recent studies have shown that being underweight is associated with a worse prognosis in various types of cancers, including colon cancer [10], hepatocellular carcinoma [11], nasopharyngeal carcinoma [12], breast cancer [13,14], cervical carcinoma [15], and urothelial carcinoma [16]. However, there is currently little information regarding the prognostic value in gastric cancer patients of being underweight [17].…”
Section: Introductionmentioning
confidence: 99%
“…These studies focused primarily on the prognostic value of being overweight or obese. On the other hand, recent studies have shown that being underweight is associated with a worse prognosis in various types of cancers, including colon cancer [10], hepatocellular carcinoma [11], nasopharyngeal carcinoma [12], breast cancer [13,14], cervical carcinoma [15], and urothelial carcinoma [16]. However, there is currently little information regarding the prognostic value in gastric cancer patients of being underweight [17].…”
Section: Introductionmentioning
confidence: 99%
“…The same is observed in our study, different rectal points RLS, RLI and RLP with correlation coefficients -0.34 (p = 0.150), -0.48 (p = 0.001) and -0.47 (p = 0.001) respectively, showing reduction in dose with increase in BMI. In contrast to this Kizer et al 17 showed patients with higher BMI to have lower rectal toxicities (compared to lower BMI) undergoing chemoradiation treatment. In another study Boyle et al 18 studied body mass index and dose to organ at risk during vaginal cuff brachytherapy with vaginal cylinders and concluded that women with higher BMI received lower bladder and small bowel dose compared to patients with lower BMI.…”
Section: Discussionmentioning
confidence: 88%
“…9 Several studies evaluated radiation induced toxicities to OARs i.e., bladder, rectum and bowel using dosimetric parameters. 10-12 Nora et al 13 studied effects of BMI on complications and survival outcomes in patients undergoing curative chemoradiotherapy for cervical carcinoma. Jihoon et al 14 studied dependence of rectal does on BMI of the patient underwent ICBT with the application of tandem and ring applicator.…”
Section: Introductionmentioning
confidence: 99%
“…In a pooled analysis of eight population-based prospective cohorts studies in Japan, Matsuo et al (2012) found a significant positive association between BMI and colorectal cancer risk in female and stronger association in male, and Morrison et al (2013) found that Increasing BMI was associated with increased hazards of death from colorectal cancer. Kizer et al (2011) analyzed the outcome of 404 patients with locally advanced cervical carcinoma and showed that the 5-year OS rate was 33%, 60%, and 68% for a BMI <18.5 kg/m 2 , a BMI from 18.5 kg/m 2 to 24.9 kg/m 2 , and a BMI >24.9 kg/m 2 , respectively and underweight patients (BMI <18.5 kg/m 2 ) had diminished OS. Kaviani et al (2013) reported that obesity was associated with poorer survival in 646 patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%